Lignin-reduced silver enhanced titanium-based antibacterial composite material, and preparation method and application thereof
Patent Information
- Application Number
- CN202410261682.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-07
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-03-07
AI Technical Summary
[0019]本发明在Ti基底表面以类贻贝材料木质素(Lignin)为粘附剂、还原剂进行表面改性,构建Ag、PLL涂层。首先,利用Lignin还原特性,Lignin中的酚和甲氧基将Ag+还原为Ag-NPs,并避免Ag-NPs的团聚,Ag-NPs释放出的带有正电荷的Ag+与带负电荷的微生物细菌膜之间静电吸引可显著促进Ag-NPs的粘附,使Ag-NPs可以在细胞壁和细胞膜上积累;其次,多聚赖氨酸(PLL)是一种带正电荷的天然存在的、生物可降解的多肽,具有良好的生物相容性,可实现细胞附着、增殖和分化,进而缩短骨愈合的时间。通过PLL与细胞之间的粘结作用,促进成骨细胞的生长增殖,改善Ti基底的抗菌及骨修复性能,从而仿生天然硬组织的优异性能,获得具有优良综合性能的无机/有机新型强效抗菌促成骨的生物医学材料。
Smart Images

Figure CN118121766B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer biomedical material production technology, and more specifically to a lignin-reduced silver-reinforced titanium-based antibacterial composite material, its preparation method, and its application. Background Technology
[0002] In recent years, with the increasing demand for implants to replace failed tissue, a near-infrared induced physiochemical synergistic therapy strategy has become increasingly important. Titanium (Ti) and titanium alloys have become the most suitable choice for clinical hard tissue repair and bone replacement due to their high strength, stress resistance, and good biocompatibility. However, bacterial infection of the titanium metal surface and poor osseointegration are two major problems hindering its clinical application.
[0003] Currently, the main methods for preparing Ti-based modified composite coatings include electrospinning, electrodeposition, and ion implantation. However, these methods suffer from slow production rates, weak coating adhesion, easy detachment, and structural changes. In-situ constructed self-assembled nanocomposites, due to their simplicity, spontaneity, scalability, and multifunctionality, have found wide application in nanotechnology and biomedical science. Studies have shown that Ti implants can be modified by loading osteogenic growth factors, active peptides, and topological structures, such as hydroxyapatite (HA), dexamethasone (Dex), and peptides, to enhance bone induction. Therefore, modification of hard tissue Ti is a current major trend.
[0004] Silver (Ag), as a broad-spectrum antibacterial agent without drug resistance, can be used as a photothermal agent (PTAs) to effectively and controllably convert absorbed near-infrared laser energy directly into heat under 808nm near-infrared (NIR) laser response, thereby generating local high temperatures, enhancing cell membrane permeability, and used for photothermal killing of bacterial pathogens; however, Ag-NPs are prone to aggregation, affecting antibacterial activity. In recent years, lignin, a mussel-like material, has been widely used in Ti surface modification due to its biocompatibility and environmental friendliness. Lignin possesses various functional groups, such as reduced phenolic hydroxyl and methoxy groups, and can act as a reducing agent and stabilizer. Its phenolic or methoxy groups can bind Ag... + Lignin-Ag is reduced to Ag-NPs, thereby constructing a uniformly distributed composite coating. However, Lignin-Ag lacks the ability to promote bone growth, which prolongs the healing time of bone defects. Summary of the Invention
[0005] To address the above problems, this invention provides a lignin-reduced silver-reinforced titanium-based antibacterial composite material, its preparation method, and its applications. This invention modifies the surface of a Ti substrate using lignin, a mussel-like material, as an adhesive and reducing agent to construct an Ag and PLL coating. This further improves the antibacterial and bone repair properties of the Ti substrate, thereby mimicking the excellent properties of natural hard tissue and obtaining a novel inorganic / organic biomedical material with excellent comprehensive properties, possessing potent antibacterial and osteogenic properties.
[0006] The first objective of this invention is to provide a method for preparing a lignin-reduced silver-reinforced titanium-based antibacterial composite material, comprising the following steps:
[0007] A mixed solution was obtained by uniformly mixing a soluble silver salt solution and a lignin solution. A titanium sheet was then immersed in the mixed solution to undergo a reduction reaction, resulting in a Ti / Lignin-Ag material.
[0008] A lignin-reduced silver-reinforced titanium-based antibacterial composite material was obtained by coating a polylysine solution onto a Ti / Lignin-Ag material and then electrostatically adsorbing the solution.
[0009] In a preferred embodiment of the present invention, the mass ratio of soluble silver salt to lignin is 0.1-0.2:1.
[0010] In a preferred embodiment of the present invention, the concentration of the soluble silver salt solution is 0.1-0.2 g / L, and the concentration of the lignin solution is 1 g / L.
[0011] In a preferred embodiment of the present invention, the concentration of the soluble silver salt solution is 0.1 g / L.
[0012] In a preferred embodiment of the present invention, the soluble silver salt is silver nitrate.
[0013] In a preferred embodiment of the present invention, the reduction reaction is performed by soaking at room temperature for 2-3 hours.
[0014] In a preferred embodiment of the present invention, the amount of polylysine solution added per square millimeter on the surface of the Ti / Lignin-Ag material is 1-2 μL, and the concentration of polylysine is 1-3 g / L.
[0015] In a preferred embodiment of the present invention, the concentration of polylysine is 1 g / L.
[0016] The second objective of this invention is to provide a lignin-reduced silver-reinforced titanium-based antibacterial composite material prepared by the above-described preparation method.
[0017] A third objective of this invention is to provide the application of the above-mentioned lignin-reduced silver-reinforced titanium-based antibacterial composite material in the preparation of antibacterial materials and osteogenic materials.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] This invention modifies the surface of a Ti substrate using lignin, a mussel-like material, as an adhesive and reducing agent to construct an Ag and PLL coating. First, utilizing the reducing properties of lignin, the phenols and methoxy groups in lignin bind Ag... + It is reduced to Ag-NPs and avoids the aggregation of Ag-NPs. The Ag-NPs release positively charged Ag. + Electrostatic attraction between Ag-NPs and negatively charged bacterial membranes significantly promotes adhesion, allowing Ag-NPs to accumulate on cell walls and membranes. Secondly, poly-L-lysine (PLL) is a positively charged, naturally occurring, biodegradable polypeptide with excellent biocompatibility, enabling cell attachment, proliferation, and differentiation, thereby shortening bone healing time. Through the adhesion between PLL and cells, osteoblast growth and proliferation are promoted, improving the antibacterial and bone repair properties of the Ti substrate. This mimics the superior properties of natural hard tissue, resulting in novel inorganic / organic biomedical materials with excellent comprehensive properties and potent antibacterial and osteogenic effects.
[0020] This invention constructs a lignin-reduced silver-reinforced titanium-based antibacterial composite material with potent photothermal and photodynamic antibacterial effects. The titanium substrate surface exhibits uniformly distributed silver nanoparticles, resulting in an antibacterial composite coating with enhanced mechanical properties and bioactivity. This method is simple to operate and low in cost, improving the bioactivity and mechanical properties of the substrate without altering its inherent properties, thus achieving a powerful bactericidal effect. Attached Figure Description
[0021] Figure 1 SEM images of Ti(a), Ti / Lignin-Ag(b), Ti / Lignin-Ag@PLL(c), and Ti / Lignin(d) composite coatings are shown; where image e is a magnified view of image b and image f is a magnified view of image d.
[0022] Figure 2 The graph shows the qualitative antibacterial data of the composite coatings prepared in Example 1, Comparative Examples 1-3 under non-photothermal conditions.
[0023] Figure 3 The graph shows the quantitative antibacterial data of the composite coatings prepared in Example 1, Comparative Examples 1-3 under non-photothermal conditions.
[0024] Figure 4 The image shows the qualitative antibacterial data of the composite coating prepared in Example 1 under photothermal conditions.
[0025] Figure 5The graph shows the quantitative data of the composite coating prepared in Example 1 under photothermal conditions.
[0026] Figure 6 Graphs showing the effects of varying silver ion concentrations (a) and polylysine concentrations (b) on osteoblast cell compatibility.
[0027] Figure 7 A graph showing the cell compatibility data of vascular endothelial cells (a) and osteoblasts (b) after varying the culture time. Detailed Implementation
[0028] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0029] In existing technologies, lignin-Ag lacks the ability to promote bone growth, which prolongs the healing time of bone defects. Therefore, this invention provides a method for preparing a lignin-reduced silver-reinforced titanium-based antibacterial composite material, comprising the following steps:
[0030] A mixed solution was obtained by uniformly mixing a soluble silver salt solution and a lignin solution. A titanium sheet was then immersed in the mixed solution to undergo a reduction reaction, resulting in a Ti / Lignin-Ag material.
[0031] A lignin-reduced silver-reinforced titanium-based antibacterial composite material was obtained by coating a polylysine solution onto a Ti / Lignin-Ag material.
[0032] This invention employs self-assembly technology to prepare a composite coating, utilizing the reduction properties of lignin; the phenol and methoxy groups in lignin bind Ag... + The process reduces the hydroxyl groups to Ag-NPs, which are then oxidized to the corresponding quinones / hydroquinones. Simultaneously, the phenolic hydroxyl groups of Lignin electrostatically interact with the amino groups of the bone-inducing agent PLL, forming a well-dispersed Ag-NPs and PLL coating on the Ti surface. During self-assembly, this technique endows the resulting inorganic and organic structures with unique properties through non-covalent interactions.
[0033] In some preferred embodiments, the mass ratio of soluble silver salt to lignin is 0.1-0.2:1;
[0034] Specifically, in the preparation of this invention, the concentration of the soluble silver salt solution is 0.1-0.2 g / L, the concentration of the lignin solution is 1 g / L, and the volume ratio of the soluble silver salt solution to the lignin solution is 1:1.
[0035] More preferably, the concentration of the soluble silver salt solution is 0.1 g / L.
[0036] The present invention involves immersing the titanium sheet in a mixed solution.
[0037] In some preferred embodiments, the soluble silver salt is silver nitrate.
[0038] In some preferred embodiments, the reduction reaction is carried out by soaking at room temperature for 2-3 hours.
[0039] In some preferred embodiments, the amount of polylysine solution added per square millimeter on the surface of the Ti / Lignin-Ag material is 1-2 μL, and the concentration of polylysine is 1-3 g / L.
[0040] More preferably, the concentration of poly-L-lysine is 1 g / L.
[0041] In some preferred embodiments, the titanium sheet used in this invention has a purity >99.9%.
[0042] The lignin-reduced silver-reinforced titanium-based antibacterial composite material prepared in this invention can be used to prepare biomedical materials that inhibit bacterial infection and promote bone healing. This is because the negatively charged microbial bacterial membrane reacts with the positively charged Ag released by Ag-NPs. + Electrostatic attraction significantly promotes the adhesion of Ag-NPs, allowing them to accumulate on the cell wall and cell membrane. Secondly, the neutralization of bacterial surface charge and the oxidative stress induced by Ag-NPs during the bactericidal process alter cell membrane permeability, leading to bacterial membrane damage and ultimately bacterial death. Furthermore, under 808nm laser irradiation, the localized heat caused by the photothermal effect accelerates the production of ROS by Ag-NPs, further damaging the bacteria.
[0043] A lignin-reduced silver-reinforced titanium-based antibacterial composite material utilizes a self-assembly technique with Ti as the substrate, grafting PLL and silver nanoparticles onto mussel-induced lignin to form a multifunctional surface. Under near-infrared radiation, it rapidly and effectively kills bacteria by generating localized high temperatures and reactive oxygen species. Simultaneously, Ag... + The release of the coating promotes vascularized bone regeneration, and the coating promotes osteoblast growth and proliferation by facilitating the adhesion between the bone material PLL and cells. A multifunctional composite coating with photoresponsive rapid antibacterial and osteopromoting properties was prepared using a rapid self-assembly technology.
[0044] This invention improves the anti-infection and bone repair properties of the substrate without altering its inherent properties, achieving rapid sterilization and bone healing. It is simple to operate and inexpensive. It solves the problems of bone defects and bacterial infections during transplantation surgery, thereby promoting bone healing. It is a photothermal antibacterial material with the potential to heal bone defects.
[0045] Unless otherwise specified, the experimental and testing methods described below are conventional methods; the reagents and raw materials described below, unless otherwise specified, are all commonly used raw materials in the field of production, all available from the market, and will not affect the production results; all the equipment used in this invention are conventional equipment used in the production process of this field, and the operation and parameters of each piece of equipment are performed in accordance with conventional operation, without any special features. The titanium sheet used in this invention has a specification of 10mm × 10mm × 1mm.
[0046] Example 1
[0047] A method for preparing a self-assembled Ti / Lignin-Ag@PLL composite material includes the following steps:
[0048] (1) Place the Ti sheet in acetone to remove oil and clean it with ultrasonic waves 3 times, each time for 10 mins;
[0049] (2) Prepare a mixed acid solution by mixing concentrated sulfuric acid, concentrated hydrochloric acid and water in a volume ratio of 1:1:1; place the Ti sheet from step (1) in the mixed acid and etch it at 60°C for 5 hours;
[0050] (3) Clean the Ti sheet from step (2) with deionized water using ultrasonic cleaning three times.
[0051] (4) Heat the Ti sheet from step (3) in a NaOH solution at 60°C for 1 hour;
[0052] (5) Clean the Ti sheet from step (4) with deionized water using ultrasonic cleaning three times.
[0053] (6) Place the Ti sheet from (5) in a 24-well plate for later use;
[0054] (7) Prepare a solution with a concentration of 1 g·L -1 A lignin solution with a concentration of 0.1 g·L⁻¹ -1 The AgNO3 solution was mixed thoroughly with the other two solutions at a volume ratio of 1:1.
[0055] (8) Take 2 mL of the mixed solution from step (7) into the well plate from step (6), soak for 2 hours, then take out the sample and let it air dry naturally to obtain the Ti / Lignin-Ag composite material.
[0056] (9) Add 100 μL of 1 g·L⁻¹ solution to the surface of the dried Ti / Lignin-Ag composite material sample. -1 The PLL solution was dried for later use to obtain the Ti / Lignin-Ag@PLL composite coating;
[0057] Example 2
[0058] A method for preparing a self-assembled Ti / Lignin-Ag@PLL composite material includes the following steps:
[0059] (1) Place the Ti sheet in acetone to remove oil and clean it with ultrasonic waves 3 times, each time for 10 mins;
[0060] (2) Prepare a mixed acid solution by mixing concentrated sulfuric acid, concentrated hydrochloric acid and water in a volume ratio of 1:1:1; place the Ti sheet from step (1) in the mixed acid and etch it at 60°C for 5 hours;
[0061] (3) Clean the Ti sheet from step (2) with deionized water using ultrasonic cleaning three times.
[0062] (4) Heat the Ti sheet from step (3) in a NaOH solution at 60°C for 1 hour;
[0063] (5) Clean the Ti sheet from step (4) with deionized water using ultrasonic cleaning three times.
[0064] (6) Place the Ti sheet from (5) in a 24-well plate for later use;
[0065] (7) Prepare a solution with a concentration of 1 g·L -1 A lignin solution with a concentration of 0.1 g·L⁻¹ -1 The AgNO3 solution was mixed thoroughly with the other two solutions at a volume ratio of 1:1.
[0066] (8) Take 2 mL of the mixed solution from step (7) into the well plate from step (6), soak for 2 hours, then take out the sample and let it air dry naturally to obtain the Ti / Lignin-Ag composite material.
[0067] (9) Add 100 μL of a 2 g·L⁻¹ solution to the surface of the dried Ti / Lignin-Ag composite material sample. -1 The PLL solution was dried for later use to obtain the Ti / Lignin-Ag@PLL composite coating;
[0068] Example 3
[0069] A method for preparing a self-assembled Ti / Lignin-Ag@PLL composite material includes the following steps:
[0070] (1) Place the Ti sheet in acetone to remove oil and clean it with ultrasonic waves 3 times, each time for 10 mins;
[0071] (2) Prepare a mixed acid solution by mixing concentrated sulfuric acid, concentrated hydrochloric acid and water in a volume ratio of 1:1:1; place the Ti sheet from step (1) in the mixed acid and etch it at 60°C for 5 hours;
[0072] (3) Clean the Ti sheet from step (2) with deionized water using ultrasonic cleaning three times.
[0073] (4) Heat the Ti sheet from step (3) in a NaOH solution at 60°C for 1 hour;
[0074] (5) Clean the Ti sheet from step (4) with deionized water using ultrasonic cleaning three times.
[0075] (6) Place the Ti sheet from (5) in a 24-well plate for later use;
[0076] (7) Prepare a solution with a concentration of 1 g·L -1 A lignin solution with a concentration of 0.1 g·L⁻¹ -1 The AgNO3 solution was mixed thoroughly with the other two solutions at a volume ratio of 1:1.
[0077] (8) Take 2 mL of the mixed solution from step (7) into the well plate from step (6), soak for 2 hours, then take out the sample and let it air dry naturally to obtain the Ti / Lignin-Ag composite material.
[0078] (9) Add 100 μL of a 3 g·L⁻¹ solution to the surface of the dried Ti / Lignin-Ag composite material sample. -1 The PLL solution was dried for later use to obtain the Ti / Lignin-Ag@PLL composite coating;
[0079] Example 4
[0080] A method for preparing a self-assembled Ti / Lignin-Ag@PLL composite material includes the following steps:
[0081] (1) Place the Ti sheet in acetone to remove oil and clean it with ultrasonic waves 3 times, each time for 10 mins;
[0082] (2) Prepare a mixed acid solution by mixing concentrated sulfuric acid, concentrated hydrochloric acid and water in a volume ratio of 1:1:1; place the Ti sheet from step (1) in the mixed acid and etch it at 60°C for 5 hours;
[0083] (3) Clean the Ti sheet from step (2) with deionized water using ultrasonic cleaning three times.
[0084] (4) Heat the Ti sheet from step (3) in a NaOH solution at 60°C for 1 hour;
[0085] (5) Clean the Ti sheet from step (4) with deionized water using ultrasonic cleaning three times.
[0086] (6) Place the Ti sheet from (5) in a 24-well plate for later use;
[0087] (7) Prepare a solution with a concentration of 1 g·L -1 A lignin solution with a concentration of 0.2 g·L⁻¹ -1 The AgNO3 solution was mixed thoroughly with the other two solutions at a volume ratio of 1:1.
[0088] (8) Take 2 mL of the mixed solution from step (7) into the well plate from step (6), soak for 2 hours, then take out the sample and let it air dry naturally to obtain the Ti / Lignin-Ag composite material.
[0089] (9) Add 100 μl of 1 g·L⁻¹ solution to the surface of the dried Ti / Lignin-Ag composite material sample. -1 The PLL solution was dried for later use to obtain the Ti / Lignin-Ag@PLL composite coating;
[0090] Example 5
[0091] A method for preparing a self-assembled Ti / Lignin-Ag@PLL composite material includes the following steps:
[0092] (1) Place the Ti sheet in acetone to remove oil and clean it with ultrasonic waves 3 times, each time for 10 mins;
[0093] (2) Prepare a mixed acid solution by mixing concentrated sulfuric acid, concentrated hydrochloric acid and water in a volume ratio of 1:1:1; place the Ti sheet from step (1) in the mixed acid and etch it at 60°C for 5 hours;
[0094] (3) Clean the Ti sheet from step (2) with deionized water using ultrasonic cleaning three times.
[0095] (4) Heat the Ti sheet from step (3) in a NaOH solution at 60°C for 1 hour;
[0096] (5) Clean the Ti sheet from step (4) with deionized water using ultrasonic cleaning three times.
[0097] (6) Place the Ti sheet from (5) in a 24-well plate for later use;
[0098] (7) Prepare a solution with a concentration of 1 g·L -1 A lignin solution with a concentration of 0.2 g·L⁻¹ -1 The AgNO3 solution was mixed thoroughly with the other two solutions at a volume ratio of 1:1.
[0099] (8) Take 2 mL of the mixed solution from step (7) into the well plate from step (6), soak for 2 hours, then take out the sample and let it air dry naturally to obtain the Ti / Lignin-Ag composite material.
[0100] (9) Add 100 μl of a 2 g·L⁻¹ solution to the surface of the dried Ti / Lignin-Ag composite material sample. -1 The PLL solution was dried for later use to obtain the Ti / Lignin-Ag@PLL composite coating;
[0101] Example 6
[0102] A method for preparing a self-assembled Ti / Lignin-Ag@PLL composite material includes the following steps:
[0103] (1) Place the Ti sheet in acetone to remove oil and clean it with ultrasonic waves 3 times, each time for 10 mins;
[0104] (2) Prepare a mixed acid solution by mixing concentrated sulfuric acid, concentrated hydrochloric acid and water in a volume ratio of 1:1:1; place the Ti sheet from step (1) in the mixed acid and etch it at 60°C for 5 hours;
[0105] (3) Clean the Ti sheet from step (2) with deionized water using ultrasonic cleaning three times.
[0106] (4) Heat the Ti sheet from step (3) in a NaOH solution at 60°C for 1 hour;
[0107] (5) Clean the Ti sheet from step (4) with deionized water using ultrasonic cleaning three times.
[0108] (6) Place the Ti sheet from (5) in a 24-well plate for later use;
[0109] (7) Prepare a solution with a concentration of 1 g·L -1 A lignin solution with a concentration of 0.2 g·L⁻¹ -1 The AgNO3 solution was mixed thoroughly with the other two solutions at a volume ratio of 1:1.
[0110] (8) Take 2 mL of the mixed solution from step (7) into the well plate from step (6), soak for 2 hours, then take out the sample and let it air dry naturally to obtain the Ti / Lignin-Ag composite material.
[0111] (9) Add 100 μl of a 3 g·L⁻¹ solution to the surface of the dried Ti / Lignin-Ag composite material sample. -1 The PLL solution was dried for later use to obtain the Ti / Lignin-Ag@PLL composite coating;
[0112] Example 7
[0113] A method for preparing a self-assembled Ti / Lignin-Ag@PLL composite material includes the following steps:
[0114] (1) Place the Ti sheet in acetone to remove oil and clean it with ultrasonic waves 3 times, each time for 10 mins;
[0115] (2) Prepare a mixed acid solution by mixing concentrated sulfuric acid, concentrated hydrochloric acid and water in a volume ratio of 1:1:1; place the Ti sheet from step (1) in the mixed acid and etch it at 60°C for 5 hours;
[0116] (3) Clean the Ti sheet from step (2) with deionized water using ultrasonic cleaning three times.
[0117] (4) Heat the Ti sheet from step (3) in a NaOH solution at 60°C for 1 hour;
[0118] (5) Clean the Ti sheet from step (4) with deionized water using ultrasonic cleaning three times.
[0119] (6) Place the Ti sheet from (5) in a 24-well plate for later use;
[0120] (7) Prepare a solution with a concentration of 1 g·L -1 A lignin solution with a concentration of 0.15 g·L⁻¹ -1 The AgNO3 solution was mixed thoroughly with the other two solutions at a volume ratio of 1:1.
[0121] (8) Take 2 mL of the mixed solution from step (7) into the well plate from step (6), soak for 3 hours, then take out the sample and let it air dry naturally to obtain the Ti / Lignin-Ag composite material.
[0122] (9) Add 200 μl of a 3 g·L⁻¹ solution to the surface of the dried Ti / Lignin-Ag composite material sample. -1 The PLL solution was dried for later use to obtain the Ti / Lignin-Ag@PLL composite coating;
[0123] Example 8
[0124] A method for preparing a self-assembled Ti / Lignin-Ag@PLL composite material includes the following steps:
[0125] (1) Place the Ti sheet in acetone to remove oil and clean it with ultrasonic waves 3 times, each time for 10 mins;
[0126] (2) Prepare a mixed acid solution by mixing concentrated sulfuric acid, concentrated hydrochloric acid and water in a volume ratio of 1:1:1; place the Ti sheet from step (1) in the mixed acid and etch it at 60°C for 5 hours;
[0127] (3) Clean the Ti sheet from step (2) with deionized water using ultrasonic cleaning three times.
[0128] (4) Heat the Ti sheet from step (3) in a NaOH solution at 60°C for 1 hour;
[0129] (5) Clean the Ti sheet from step (4) with deionized water using ultrasonic cleaning three times.
[0130] (6) Place the Ti sheet from (5) in a 24-well plate for later use;
[0131] (7) Prepare a solution with a concentration of 1 g·L -1 A lignin solution with a concentration of 0.2 g·L⁻¹ -1 The AgNO3 solution was mixed thoroughly with the other two solutions at a volume ratio of 1:1.
[0132] (8) Take 2 mL of the mixed solution from step (7) into the well plate from step (6), soak for 2 hours, then take out the sample and let it air dry naturally to obtain the Ti / Lignin-Ag composite material.
[0133] (9) Add 150 μl of a 3 g·L⁻¹ solution to the surface of the dried Ti / Lignin-Ag composite material sample. -1 The PLL solution was dried for later use to obtain the Ti / Lignin-Ag@PLL composite coating;
[0134] Comparative Example 1
[0135] After treating the Ti in this comparative example, it was set aside for later use. The specific preparation steps are as follows:
[0136] (1) Place the Ti sheet in acetone to remove oil and clean it with ultrasonic waves 3 times, each time for 10 mins;
[0137] (2) Prepare a mixed acid solution by mixing concentrated sulfuric acid, concentrated hydrochloric acid and water in a volume ratio of 1:1:1; place the Ti sheet from step (1) in the mixed acid and etch it at 60°C for 5 hours;
[0138] (3) Clean the Ti sheet from step (2) with deionized water using ultrasonic cleaning three times.
[0139] (4) Heat the Ti sheet from step (3) in a NaOH solution at 60°C for 1 hour;
[0140] (5) Clean the Ti sheet from step (4) with deionized water using ultrasonic cleaning three times.
[0141] (6) Place the Ti sheet from (5) in a 24-well plate for later use, and denote it as Ti;
[0142] Comparative Example 2
[0143] A method for preparing a self-assembled Ti / Lignin composite material includes the following steps:
[0144] (1) Place the Ti sheet in acetone to remove oil and clean it with ultrasonic waves 3 times, each time for 10 mins;
[0145] (2) Prepare a mixed acid solution by mixing concentrated sulfuric acid, concentrated hydrochloric acid and water in a volume ratio of 1:1:1; place the Ti sheet from step (1) in the mixed acid and etch it at 60°C for 3-5 hours.
[0146] (3) Clean the Ti sheet from step (2) with deionized water using ultrasonic cleaning three times.
[0147] (4) Heat the Ti sheet from step (3) in a NaOH solution at 60°C for 1 hour;
[0148] (5) Clean the Ti sheet from step (4) with deionized water using ultrasonic cleaning three times.
[0149] (6) Place the Ti sheet from (5) in a 24-well plate for later use;
[0150] (7) Prepare a solution with a concentration of 1 g·L -1 lignin solution;
[0151] (8) Take 2 mL of the solution from step (7) into the well plate from step (6), soak for 2 hours, then take out the sample and let it air dry naturally to obtain the Ti / Lignin composite material.
[0152] Comparative Example 3
[0153] A method for preparing a self-assembled Ti / Lignin-Ag composite material includes the following steps:
[0154] (1) Place the Ti sheet in acetone to remove oil and clean it with ultrasonic waves 3 times, each time for 10 mins;
[0155] (2) Prepare a mixed acid solution by mixing concentrated sulfuric acid, concentrated hydrochloric acid and water in a volume ratio of 1:1:1; place the Ti sheet from step (1) in the mixed acid and etch it at 60°C for 5 hours;
[0156] (3) Clean the Ti sheet from step (2) with deionized water using ultrasonic cleaning three times.
[0157] (4) Heat the Ti sheet from step (3) in a NaOH solution at 60°C for 1 hour;
[0158] (5) Clean the Ti sheet from step (4) with deionized water using ultrasonic cleaning three times.
[0159] (6) Place the Ti sheet from (5) in a 24-well plate for later use;
[0160] (7) Prepare a solution with a concentration of 1 g·L -1 A lignin solution with a concentration of 0.1 g·L⁻¹ -1 The AgNO3 solution was mixed thoroughly with the other two solutions at a volume ratio of 1:1.
[0161] (8) Take 2 mL of the mixed solution from step (7) into the well plate from step (6), soak for 2 hours, then take out the sample and let it air dry naturally to obtain the Ti / Lignin-Ag composite material.
[0162] Comparative Example 4
[0163] A method for preparing a self-assembled Ti / Lignin-Ag composite material includes the following steps:
[0164] (1) Place the Ti sheet in acetone to remove oil and clean it with ultrasonic waves 3 times, each time for 10 mins;
[0165] (2) Prepare a mixed acid solution by mixing concentrated sulfuric acid, concentrated hydrochloric acid and water in a volume ratio of 1:1:1; place the Ti sheet from step (1) in the mixed acid and etch it at 60°C for 5 hours;
[0166] (3) Clean the Ti sheet from step (2) with deionized water using ultrasonic cleaning three times.
[0167] (4) Heat the Ti sheet from step (3) in a NaOH solution at 60°C for 1 hour;
[0168] (5) Clean the Ti sheet from step (4) with deionized water using ultrasonic cleaning three times.
[0169] (6) Place the Ti sheet from (5) in a 24-well plate for later use;
[0170] (7) Prepare a solution with a concentration of 1 g·L -1 A lignin solution with a concentration of 0.2 g·L⁻¹ -1 The AgNO3 solution was mixed thoroughly with the other two solutions at a volume ratio of 1:1.
[0171] (8) Take 2 mL of the mixed solution from step (7) into the well plate from step (6), soak for 2 hours, then take out the sample and let it air dry naturally to obtain the Ti / Lignin-Ag composite material.
[0172] Depend on Figure 1 (Example 1) It can be seen that uniform Ag-NPs are formed on the Ti surface, with a uniform morphology and a particle size of about 100 nm; through electrostatic interaction, PLL with bone induction properties are self-assembled, and the coating surface presents a thin film.
[0173] Photothermal antibacterial experiments were conducted on the composite coatings prepared in Example 1 and Comparative Examples 1-3:
[0174] Strains: The strains used in this invention are Escherichia coli (E. coli) purchased from Beina Biotechnology, strain number BNCC336902, and Staphylococcus aureus (S. aureus) strain number ATCC25923.
[0175] Experimental conditions: E. coli and S. aureus strains were inoculated on MH agar medium and cultured at 37°C for 12 hours. A bacterial suspension with a concentration of 0.5 McF was prepared, and 50 μL was dropped onto the coating. After culturing at 37°C for 24 hours, the bacteria on the material surface were plated using an inoculation loop and cultured at 37°C for 24 hours under both light and dark conditions. Qualitative and quantitative analysis was then performed.
[0176] (1) No light conditions refer to: bacterial culture time of 24h and temperature of 37℃ under no light conditions;
[0177] (2) Illumination conditions refer to: under illumination conditions, first irradiate with near-infrared light for 10 minutes, with a power of 1.0 W·cm. -2 Bacterial culture for 3 hours; results are shown below. Figure 2 As shown.
[0178] Results Analysis: Figure 2 It can be seen that after bacteria are incubated on the material surface for 24 hours, Ti has no bactericidal ability, and the bacteria on the surface have vigorous metabolism, forming accumulated E. coli and S. aureus colonies; the number of E. coli and S. aureus colonies in Ti / Lignin is slightly reduced, while the number of E. coli and S. aureus colonies in Ti / Lignin-Ag (Comparative Example 3) and Ti / Lignin-Ag@PLL (Example 1) is significantly reduced. Figure 3 In the study, the antibacterial rates of Ti and Lignin coatings against E. coli and S. aureus were both 0%, while the antibacterial rates of Ti / Lignin-Ag surface against E. coli and S. aureus were 80% and 90%, respectively. The addition of PLL had little effect on the antibacterial rate of the composite coating.
[0179] To verify the rapid bactericidal effect achieved by the composite coating through the synergistic effect of photothermal and photodynamic processes, the Ti / Lignin-Ag@PLL composite coating prepared in Example 1 was used as an example. E. coli and S. aureus were incubated on the surface of the Ti / Lignin-Ag@PLL composite coating under both unirradiated and irradiated conditions. After 24 hours of culture without irradiation, bacteria covered the coating surface, indicating poor antibacterial effect. After irradiation with an 808nm laser, no E. coli or S. aureus colonies were found on the surface of the Ti / Lignin-Ag@PLL coating. Both quantitative and qualitative experimental results showed that the antibacterial rate against E. coli and S. aureus reached 100% on the light-irradiated Ti / Lignin-Ag@PLL composite coating surface, demonstrating strong photothermal antibacterial ability against these two bacteria.
[0180] Culture of osteoblasts (OBs) and vascular endothelial cells (VECs) was conducted in eight experimental groups, including Ti and different Ag groups. + Ti / Lignin-Ag (0, 0.1, 0.2 g·L⁻¹) were prepared at different concentrations. -1 Ti / Lignin-Ag@PLL (0, 1, 2, 3 g·L⁻¹) were prepared with different PLL concentrations. -1 Each group has 7 parallel samples.
[0181] A Ti / Lignin-Ag@PLL composite coating was prepared on a titanium surface using a self-assembly technique. First, a coating with a concentration of 1 g·L⁻¹ was prepared. -1 A lignin solution was prepared, followed by AgNO3 solutions of different concentrations (0 g·L⁻¹). -1 0.1 g·L -1 0.2 g·L -1 Add the prepared AgNO3 solution dropwise to the lignin solution and mix well. Place the titanium sheet in a 24-well plate and add 2 ml of Lignin / AgNO3 solution to each well. After soaking for 2 hours, remove the sample and let it air dry naturally. See Comparative Examples 2-4 for details.
[0182] Result: From Figure 6 As shown in Figure a, one day after OBs were vaccinated, Ag... + The concentration is 0.10 g·L. -1 At that time, osteoblast activity was highest on the surface of the composite coating, Ag + The concentration is 0.20 g·L. -1 At that time, the osteoblast activity on its surface was lowest; 3-7 days after inoculation, Ag + The concentration is 0.10 g·L. -1At that time, osteoblast activity was highest on the surface of the composite coating. Overall, Ag... + The concentration is 0.10 g·L. -1 As the number of culture days increased, the osteoblast activity on the surface of the composite coating gradually increased, and the activity was the highest compared to other groups.
[0183] Below, we will use Ag + The concentration is 0.10 g·L. -1 100 μL of PLL solution of different concentrations (0 g·L⁻¹) was dropped onto the surface of the prepared sample. -1 1g·L -1 2g·L -1 3g·L -1 (The samples were then dried and ready for use. See Comparative Example 3 and Examples 1-3 for details.)
[0184] Depend on Figure 6 As shown in Figure b, the PLL concentration was 1 g·L⁻¹ during days 1-7 after OBs inoculation. -1 The Ti / Lignin-Ag@PLL composite coating exhibited the highest osteoblast activity at a PLL concentration of 2-3 g·L⁻¹. -1 The higher the concentration of PLL, the lower the cell viability, and the concentration of PLL is 2-3 g·L. -1 The cell viability on the composite coating surface was lower than that on Ti / Lignin-Ag without PLL. In general, osteoblast activity gradually increased with increasing culture days, and the composite coating containing PLL was more conducive to the cell viability of OBs.
[0185] In summary, the optimal conditions for preparing the Ti / Lignin-Ag@PLL composite coating are Ag + The concentration is 0.10 g·L. -1 The PLL concentration is 1 g·L⁻¹ -1 The composite coating prepared under these optimized conditions was analyzed for properties such as cell compatibility.
[0186] Figure 7 Figure (a) shows the cell compatibility of vascular endothelial cells (VECs) after changing the culture time; Figure 7 Figure (b) shows the cell compatibility of osteoblasts (OBs) after changing the parameters;
[0187] Because a large number of capillaries are distributed around human bones, responsible for the transport of oxygen and other nutrients, vascular endothelial cells (VECs) are studied. Figure 7(a) It can be seen that from day 1 to day 3, there was no significant difference in cell activity on different coatings. The cell activity on the Ti / Lignin-Ag@PLL surface prepared in Example 1 was the highest, followed by the Ti / Lignin-Ag prepared in Comparative Example 3, and finally the Ti / Lignin prepared in Comparative Example 2. From day 5 to day 7, the cell activity on the Ti / Lignin-Ag@PLL surface was the highest, showing a significant difference from the other groups. Furthermore, with the extension of time, the VECs cell activity on the Ti / Lignin-Ag@PLL surface prepared in Example 1 gradually increased. In summary, the Ti / Lignin-Ag@PLL composite coating has good compatibility with VECs, can promote the growth and proliferation of VECs, and has angiogenesis capabilities.
[0188] Since osteoblasts (OBs) are the main functional cells that promote bone formation in the human body, this study focuses on OBs as the primary functional cells for bone formation. Figure 7 (b) It was found that after 1-3 days of culture, cell growth on the surface of the Ti and Ti / Lignin composite coatings was poor. There was no significant difference between the Ti / Lignin prepared in Comparative Example 2, the Ti / Lignin-Ag prepared in Comparative Example 3, and the Ti / Lignin-Ag@PLL prepared in Example 1. After 5-7 days of cell culture, osteoblast activity on the surface of the composite coatings after the introduction of Ag and PLL increased. The cell activity on the Ti / Lignin-Ag@PLL surface was the highest, followed by Ti / Lignin-Ag, and finally Ti and Ti / Lignin. Furthermore, with the extension of time, the activity of OBs cells on the surface of the Ti / Lignin-Ag@PLL prepared in Example 1 gradually increased. In conclusion, the composite coating with the addition of Ag and PLL is more conducive to promoting the growth of OBs, and the Ti / Lignin-Ag@PLL composite coating has good osteoinductive properties.
[0189] Although preferred embodiments of the invention have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including both the preferred embodiments and all changes and modifications falling within the scope of the invention.
[0190] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.
Claims
1. A method for preparing a lignin-reduced silver-reinforced titanium-based antibacterial composite material, characterized in that, Includes the following steps: A mixed solution was obtained by uniformly mixing a soluble silver salt solution and a lignin solution. A titanium sheet was then immersed in the mixed solution to undergo a reduction reaction, resulting in a Ti / Lignin-Ag material. A lignin-reduced silver-reinforced titanium-based antibacterial composite material was obtained by coating a polylysine solution onto a Ti / Lignin-Ag material and then electrostatically adsorbing it. The mass ratio of soluble silver salt to lignin is 0.1-0.2:
1. The amount of polylysine solution added per square millimeter on the surface of Ti / Lignin-Ag material is 1-2 μL, and the concentration of polylysine is 1-3 g / L.
2. The preparation method of the lignin-reduced silver-reinforced titanium-based antibacterial composite material according to claim 1, characterized in that, The concentration of the soluble silver salt solution is 0.1-0.2 g / L, and the concentration of the lignin solution is 1 g / L.
3. The method for preparing a lignin-reduced silver-reinforced titanium-based antibacterial composite material according to claim 1, characterized in that, The soluble silver salt is silver nitrate.
4. The method for preparing a lignin-reduced silver-reinforced titanium-based antibacterial composite material according to claim 1, characterized in that, The reduction reaction is achieved by soaking at room temperature for 2-3 hours.
5. A lignin-reduced silver-reinforced titanium-based antibacterial composite material prepared by the preparation method according to any one of claims 1-4.
6. The application of the lignin-reduced silver-reinforced titanium-based antibacterial composite material according to claim 5 in the preparation of antibacterial materials and osteogenic materials.
Citation Information
Patent Citations
Double-photoresponse type zinc oxide, preparation method thereof and photosensitive coating with antibacterial osteogenesis
CN111646495A
Aqueous electrophoretic deposition
US20110168558A1